Gender Differences in Preclinical Markers of Kidney Injury in a Rural North Carolina African-American Cohort - Pointer, Mildred A.; Hicks, Kianda; Williams-Devane, ClarLynda; Wells, Candace; Greene, Natasha (Frontiers in Public Health, 2015)
Introduction: The incidence rate of end-stage renal disease (ESRD) is highest among African American (AA) males. The reason for this disparity in ESRD for AA males remains unclear but it is well established that diabetes is the leading risk factor. Prediabetes may also be a risk for kidney disease since prediabetics have increased risk for cardiovascular disease and prediabetics often do not receive drug interventions unless their hemoglobin A1c (A1c) level is above 6%. Perhaps AA males are at greater risk because they often are untreated prediabetics and this predisposes them to renal injury. Therefore, we hypothesize that prediabetic AA males have higher albumin:creatinine ratio (ACr), a biomarker of renal injury, than their female counterparts. Methods: Male and female AAs were recruited (53 females and 47 males; 45 ± 2 years old) from a rural northeastern region of NC. Blood and urine samples were collected for A1c and albumin measurements, respectively. Participants were stratified based on their A1c levels: non-diabetic: < 5.7%, pre-diabetic: ≥ 5.7% but <6.5%, and diabetic: ≥ 6.5%. Results: The proportion of males that are normal, prediabetic, and diabetic differed from that of females (p=0.002). Interestingly, prediabetic men tended to be younger (41 ± 4 vs. 51 ± 3, respectively; p=0.027) than prediabetic females (p=0.027). A1c and ACr were not associated with blood pressure in males or females. AA males had a relative risk of 0.9, 2.5, and 1.4 for microalbuminuria for non-diabetic, prediabetic, and diabetic, respectively, compared to AA females. Conclusion: These results support our hypothesis that AA males may be predisposed to prediabetes kidney injury compared to their female counterpart. Thus, young AA males should be screened for biomarkers of kidney injury even if they have normal glucose and blood pressure levels.